HopA1 Effector from Pseudomonas syringae pv syringae Strain 61 Affects NMD Processes and Elicits Effector-Triggered Immunity - Dahale, Shraddha K. (Int J Mol Sci, 2021)
Pseudomonas syringae-secreted HopA1 effectors are important determinants in host range expansion and increased pathogenicity. Their recent acquisitions via horizontal gene transfer in several non-pathogenic Pseudomonas strains worldwide have caused alarming increase in their virulence capabilities. In Arabidopsis thaliana, RESISTANCE TO PSEUDOMONAS SYRINGAE 6 (RPS6) gene confers effector-triggered immunity (ETI) against HopA1(pss) derived from P. syringae pv. syringae strain 61. Surprisingly, a closely related HopA1(pst) from the tomato pathovar evades immune detection. These responsive differences in planta between the two HopA1s represents a unique system to study pathogen adaptation skills and host-jumps. However, molecular understanding of HopA1′s contribution to overall virulence remain undeciphered. Here, we show that immune-suppressive functions of HopA1(pst) are more potent than HopA1(pss). In the resistance-compromised ENHANCED DISEASE SUSCEPTIBILITY 1 (EDS1) null-mutant, transcriptomic changes associated with HopA1(pss)-elicited ETI are still induced and carry resemblance to PAMP-triggered immunity (PTI) signatures. Enrichment of HopA1(pss) interactome identifies proteins with regulatory roles in post-transcriptional and translational processes. With our demonstration here that both HopA1 suppress reporter-gene translations in vitro imply that the above effector-associations with plant target carry inhibitory consequences. Overall, with our results here we unravel possible virulence role(s) of HopA1 in suppressing PTI and provide newer insights into its detection in resistant plants.